Patients' perspective on a pill-in-the-pocket oral anticoagulation as an alternative stroke prevention strategy in atrial fibrillation. (19th May 2022) - Briosa E Gala, A; Pope, MTB; Leo, M; Lobban, T; Betts, TR
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Oral anticoagulation (OAC) decisions are binary: if atrial fibrillation (AF) is detected and additional risk factors are presented, lifelong continuous OAC is recommended regardless of AF burden or temporal patterns. AF-related stroke risk appears to be lower in patients with paroxysmal AF and, therefore, indefinite OAC may have limited benefit whilst exposing patients to a significant bleeding risk. 'Pill-in-the-pocket' OAC during and shortly after AF challenges this dichotomous approach to OAC and is being explored in several pilot studies as an alternative AF-related stroke prevention strategy. Purpose: This patient questionnaire sought to examine patients' perspective of 'pill-in-the pocket' OAC strategy. Methods: An 8-question interactive survey was developed in collaboration with AF Association (UK based charity) and included a short description of implantable cardiac monitors main features, implant procedure and associated risks. The survey was available online on the AF Association website from 30/09/2020 to 2/11/2020. Results: Overall, 321 participants with an underlying diagnosis of AF replied to the online survey over the course of four and half weeks. The majority (82%) were taking direct oral anticoagulants. Just over two thirds of patients had concerns regarding bleeding side-effects from taking OAC and, approximately, a quarter had experienced a bleeding event (1.5% major bleeding and 24.2% minor bleeding). When asked if it was shown to be safe to monitor their heart rhythm continuously and take anticoagulants only during an episode of AF and for a small number of days afterwards (i.e. 'pill-in-the-pocket'), 53.7% of participants would use guided by an implantable cardiac monitored. Slightly lower number of patients (48%) would take pill-in-the-pocket oral anticoagulation guided by a wearable device. In the comments the main reasons not to pursue 'pill-in-the-pocket' were permanent AF, previous thromboembolic events and concerns regarding reliability of monitoring technologies. In contrast, those who were receptive to this alternative approach had previous bleeding episodes, had very infrequent AF episodes and wanted to reduce their medication burden. Conclusion: Approximately half of patients with choose a 'pill-in-the-pocket' OAC guided by daily rhythm monitoring with an ICM if proven to be safe and effective at reducing thromboembolism.